Pengaruh Harga dan Kualitas Produk Terhadap Kepuasan Konsumen Restoran Foodpedia Pasar Baru - Sefanya Erlivia; Donant Alananto Iskandar (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine how much influence price and product quality have on consumer satisfaction at the Pasar Baru foodpedia restaurant. This research method is quantitative and the data collection process is done by distributing questionnaires. This research uses non-probability sampling technique. The results of the research from 110 respondents who were processed using the SPSS program showed that the price variable had an effect on consumer satisfaction with a t-count value of 3.662 > 1.979. Product quality variable t value is 4,501 > 1,979. While the price variable (X1) and product quality (X2) together have an effect on the consumer satisfaction variable (Y) with the calculated F value > F table value (44.239 > 3.07). Thus, H0 is rejected, Ha is accepted, which means that the price variable (X1) and product quality (X2) if tested together or simultaneously affect the consumer satisfaction variable (Y).